Creditor's Legal Protection Related to Debtor's Default in A Joint Venture Partnership - Ratna Damayanti; Maman Sudirman (Pelopor Publikasi Akademika, 2024)
In order to increase national development with an emphasis on the economic and business sectors, considerable capital support is required. The capital can be obtained from various sources, one of which comes from loan or credit facilities provided by banks. Money lending activities or better known as credit in daily life practice are not something strange anymore, in fact, this credit term is not only known by urban people, but also to people in rural areas. Credit generally functions to facilitate a business activity, and especially for economic activities in Indonesia plays a very important role in its position, both for production businesses and private businesses that are developed independently because they aim to improve the standard of living of the community. Default can occur both due to intentional factors and factors beyond human ability. This research method uses a normative juridical research method with a legislative and conceptual approach. The data sources of this research are primary, secondary and tertiary data sources. The technique of collecting legal materials is used through literature study. And the analysis of legal materials is carried out by interpreting the law and the method of legal construction. The legal interpretation and construction techniques used are grammatical interpretation and analogous construction which is carried out to fully describe the Legal Protection of Creditors Related to Debtor Default in the Covenant Agreement.